2004
DOI: 10.1002/ceat.200407031
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Vanadia‐Titania Catalysts with Hierarchical Architecture in the Oxyhydrative Scission of 1‐Butene to Acetic Acid

Abstract: The synthesis of hierarchically designed supported vanadia‐titania catalysts and their properties in the oxyhydrative scission (OHS) of 1‐butene to acetic acid (AA) is described. The interaction of the TiO2 support with V2O5 appears to be responsible for an enhanced catalytic performance, and it is proposed that the catalytic activity is related to the number and size of the contact zones between the support and the active component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…To achieve optimal performances, hierarchical structures with controlled crystalline structures and spatial distribution of each component are often desired. 13 Electrospinning allows convenient fabrication of hierarchically structured oxide materials with high porosity, surface area, as well as controlled compositions and sizes. In particular, electrospun nanofibers are small in diameter but long in length, which makes it very convenient to study both their microstructure (as shown in this work) and their macroscopic properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve optimal performances, hierarchical structures with controlled crystalline structures and spatial distribution of each component are often desired. 13 Electrospinning allows convenient fabrication of hierarchically structured oxide materials with high porosity, surface area, as well as controlled compositions and sizes. In particular, electrospun nanofibers are small in diameter but long in length, which makes it very convenient to study both their microstructure (as shown in this work) and their macroscopic properties.…”
mentioning
confidence: 99%
“…Mixed oxides are widely used in many technologically important fields such as catalysis, chemical sensing, and rechargeable batteries. To achieve optimal performances, hierarchical structures with controlled crystalline structures and spatial distribution of each component are often desired . Electrospinning allows convenient fabrication of hierarchically structured oxide materials with high porosity, surface area, as well as controlled compositions and sizes.…”
mentioning
confidence: 99%